Internet and its Use in University Library - Mysore: a Case Study - Saraswathi, P.; Giddaiah, D. (Journal of Information and Knowledge, 2010)
The study is indented to elicit opinions from the users of Internet Centre of University Library, Mysore, regarding the exploitation of Internet resources. A Questionnaire was used to make a survey of Internet facilities at the Internet Centre, University Library, Mysore. The analysis of the data thus covers "characteristics of study population, purposes of Internet use, most used Internet services, problems faced by the users while using the Internet services and suggestion made by the users for the future improvement of Internet services at Internet Centre, University Library- Mysore.